ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN IBU HAMIL DALAM MENGHADAPI PERSALINAN - Viqy Lestaluhu (Jurnal Kebidanan, 2023)
Anxiety in pregnancy is an emotional reaction that occurs in pregnant women related to the mother's concern for the welfare of herself and her fetus, the continuity of pregnancy, childbirth, the period after delivery and when she has played the role of being a mother. Every pregnant woman has a different level of anxiety and is very dependent on the extent to which the pregnant woman perceives her pregnancy. This study aims to determine the factors associated with the anxiety of pregnant women in facing childbirth. The type of research used is quantitative with a cross-sectional research design. The number of samples taken was 30 people with the Consecutive Sampling technique. The instrument used is a questionnaire. The data obtained was then analyzed with the Chi Square test. The results showed that there was a significant relationship between age and the anxiety of pregnant women facing childbirth (p value = 0.04). In addition, there is a significant relationship between education andparity with the anxiety of pregnant women facing childbirth (p value = 0.034 and p value = 0.01). Therefore, it is hoped that health workers can provide counseling related to the anxiety experienced by pregnant women so that anxiety can be overcome.